Censura e erotismo na literatura de Cassandra Rios - Sousa, Juliana Moreira de (2020)
This work aims to propose a reading of the novels Copacabana Posto 6 – A Madrasta (1956); A noite tem mais luzes (1960); A borboleta branca (1962); A breve história de Fábia (1964) and As traças (1975), by the brazilian author Cassandra Rios. Despite the writer’s relevant contribution to the female homoerotic themed literature in Brazil, her work only became academic research object very recently, in the 2000’s decade, thanks to de Cultural Studies’ presence as a way of reading, but it is still scarcely analyzed. As a result, we chose to work with her books from two perspectives: censorship and eroticism. The choice to evaluate the aspect of censorship happened because Cassandra Rios had a big part of her publications forbidden before and during the military dictatorship in Brazil, therefore, it’s an important element of her writing and publication process. For the comprehension of this literary field under censorship, we used references like Maria Luiza Carneiro (1997), Paolo Marconi (1980), Creuza Berg (2008), Sandra Reimão (2011) and Carlos Fico (2012). The perspective of the analysis of erotic, in turn, came from its constant presence in the author’s work, as well as from its singular relationship with the first point. As theoretical scope for this analysis, we worked in two moments: one with the link between erotic and pornographic, grounded on Eliane Moraes’ (2003) e Nuno Cesar Abreu’s (2012) researches, and the other one with the transgressor capacity of eroticism based on the reading of Bataille (2013). In addition, we selected five novels because we believe that, as it is a literary project, we have to analyze these elements in different moments of the writer’s production. From this path, we also realized that both eroticism and censorship, in their relationship with the novels, had an affinity with the lesbian characters’ presence, which is an important feature of Cassandra Rios’ literary project. In the quest to understand this aspect, we also count on the works of Mara Faury (1984); Judith Butler (2003); Lucia Facco (2004) and Monique Wittig (2019).